The global burden of chronic urticaria for the patient and society. (2nd November 2020) - Gonçalo, M.; Gimenéz‐Arnau, A.; Al‐Ahmad, M.; Ben‐Shoshan, M.; Bernstein, J.A.; Ensina, L.F.; Fomina, D.; Galvàn, C.A.; Godse, K.; Grattan, C.; Hide, M.; Katelaris, C.H.; et al.
Summary: Chronic urticaria (CU) affects about 1% of the world population of all ages, mostly young and middle‐aged women. It usually lasts for several years (> 1 year in 25–75% of patients) and often takes > 1 year before effective management is implemented. It presents as chronic spontaneous urticaria (CSU), chronic inducible urticaria (CIndU) or both in the same person. More than 25% of cases are resistant to H1 ‐antihistamines, even at higher doses, and third‐ and fourth‐line therapies (omalizumab and ciclosporin) control the disease only in two‐thirds of H1 ‐antihistamine‐resistant patients. Here we review the impact of CU on different aspects of patients' quality of life and the burden of this chronic disease for the patient and society. CU may have a strong impact on health‐related quality of life (HRQoL), particularly when CSU is associated with angio‐oedema and/or CIndU (Dermatology Life Quality Index > 10 in 30% of patients). Comorbidities, such as anxiety and depression, which are present in more than 30% of patients with CSU, compound HRQoL impairment. Severe pruritus and the unpredictable occurrence of weals and angio‐oedema are responsible for sleep disorders; sexual dysfunction; limitations on daily life, work and sports activities; interfering with life within the family and in society; and patients' performance at school and work (6% absenteeism and 25% presenteeism). Apart from treatment costs, with annual values between 900 and 2400 purchasing power parity dollars (PPP) in Europe and the USA, CU is associated with a high consumption of medical resources and other indirect costs, which may reach a total annual cost of PPP 15 550. Abstract : Plain language summary available online